Residual seawater from salt production (bittern) as a coagulant to remove lead (Pb2+) and turbidity from batik industry wastewater - Eddy Setiadi Soedjono (Elsevier, 2021)
Coagulation and flocculation using bittern coagulant are effective methods for processing batik industrial wastewater containing heavy metals and high turbidity. Bittern as residual seawater product from salt production can be used as a natural coagulant as it contains magnesium (Mg2+), chloride (Cl−), and sulfate ions (SO42-) which can react with Pb2+ and turbidity to produce precipitation. This study focused on Pb2+ and turbidity removal from batik wastewater by introducing different variations of coagulant doses and variations in fast-stirring speed. Bittern coagulant dosage (v/v) of 5%, 15%, 25%, and 35% were used while fast-stirring speed were 55 rpm, 90 rpm, and 125 rpm. Results of this experiment showed that variations of coagulants and stirring speed to give Pb2+ maximum removal of 99.3% happened when coagulant dose and stirring speed at 35% and 55 rpm, while maximum turbidity removal at 97% happened when coagulant dose and stirring speed was 15 % and 125 rpm, respectively. Optimum dose using Response Surface Methodology (RSM) was at coagulant dose of 25% with 55 rpm, of which Pb2+ and turbidity removal were 99% and 93%, respectively.